2004
DOI: 10.1016/j.ejpain.2003.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Pain and PTSD symptoms in female veterans⋆,⋆⋆

Abstract: These results indicate that the association between pain and PTSD symptoms, previously observed in primarily male samples, is generalisable to females. Clinical implications and possible mechanisms of association are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
67
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 19 publications
8
67
6
Order By: Relevance
“…Our findings suggest that mutual maintenance may play an important role in the early aftermath of trauma only and is in line with a recent study, which found peritraumatic pain, but not persistent pain, as a risk factor for later PTSD (Norman et al 2008). Second, there may be a pre-existing vulnerability factor such as anxiety sensitivity, increasing the likelihood of the development of both disorders (Asmundson et al 2002;Asmundson et al 2004). Anxiety sensitivity, i.e.…”
supporting
confidence: 78%
“…Our findings suggest that mutual maintenance may play an important role in the early aftermath of trauma only and is in line with a recent study, which found peritraumatic pain, but not persistent pain, as a risk factor for later PTSD (Norman et al 2008). Second, there may be a pre-existing vulnerability factor such as anxiety sensitivity, increasing the likelihood of the development of both disorders (Asmundson et al 2002;Asmundson et al 2004). Anxiety sensitivity, i.e.…”
supporting
confidence: 78%
“…In contrast, a study of Vietnam veterans presenting for outpatient treatment of PTSD revealed that 80 percent also reported experiencing chronic pain, although they did not specify the type of pain (e.g., back pain, arthritis), and the chronic pain diagnosis was not confirmed by their doctors [39]. Another study indicated that female veterans who used Department of Veterans Affairs (VA) services reported levels of comorbidity consistent with those reported by males [40]. However, this study did not specifically examine patients with PTSD but rather all female veterans using VA services; self-report of pain problems was used rather than actual diagnoses.…”
Section: Introductionmentioning
confidence: 76%
“…For veterans with PTSD, Shipherd et al found that 66 percent had a comorbid diagnosis of chronic pain. * Asmundson et al reported that 44 percent of female veterans with PTSD (full or subsyndromal) scored higher on pain experience and pain interference ratings (i.e., how much pain interfered with daily functioning) [2]. For a group of firefighters with PTSD, McFarlane et al found that approximately 45 percent reported significant back pain [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that posttraumatic stress disorder (PTSD) and chronic pain frequently co-occur [1][2]. Persons with PTSD commonly report chronic pain, and persons with chronic pain report more severe PTSD symptoms [3][4].…”
Section: Introductionmentioning
confidence: 99%